1986
DOI: 10.1203/00006450-198603000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Uptake, Utilization, and Transfer by the Human Placenta as Functions of Maternal Glucose Concentration

Abstract: ABSTRACT. The impact of varying maternal glucose concentrations on glucose uptake, transfer, and metabolism was investigated in the human placenta perfused in vitro. The rates of placental glucose uptake from the maternal perfusate and transfer to the fetal perfusate were significantly correlated with maternal glucose concentration up to 20 mM. Placental glucose utilization was also dependent upon maternal glucose concentration up to 17 mM. Between 3 and 53 mM maternal glucose, lactate production increased 3-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(35 citation statements)
references
References 19 publications
2
29
1
3
Order By: Relevance
“…The release of lactate by the placenta was not affected by maternal glucose concentration. This is consistent with previous perfusion studies which showed that the rate of lactate production was not affected by maternal glucose concentrations ranging from 5.5 to 53 mmol/l [12]. The HPLC results suggest that during the time of the experiment (1.5 h), the pool of glucose used for lactate production is independent of the glucose being transported from the maternal perfusate to the fetal effluent.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The release of lactate by the placenta was not affected by maternal glucose concentration. This is consistent with previous perfusion studies which showed that the rate of lactate production was not affected by maternal glucose concentrations ranging from 5.5 to 53 mmol/l [12]. The HPLC results suggest that during the time of the experiment (1.5 h), the pool of glucose used for lactate production is independent of the glucose being transported from the maternal perfusate to the fetal effluent.…”
Section: Discussionsupporting
confidence: 81%
“…The syncytiotrophoblast, therefore, should have considerable capacity for nutrient buffering. This has been shown to occur at least to some degree for glucose metabolism in non-diabetic human perfused placentae [12].…”
mentioning
confidence: 99%
“…Net glucose utilisation was reduced in both GDM groups compared with non-diabetic control subjects and did not increase markedly with increased maternal glucose concentration. Lactate release from the perfused placenta has previously been measured but the comparison of GDM and normal placentae has not been studied [17]. Placental lactate production by the placenta is a normal, aerobic process and not the result of oxygen deficit [18].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitously expressed GLUT-1 isoform is inversely related to extracellular glucose concentration in placenta (17) whereas GLUT-4, which is found to a lesser extent in the placenta, are insulin sensitive GLUTs (18). Studies have demonstrated diminished glucose uptake in placental tissue from individuals with GDM (19)(20)(21)(22) and furthermore, increased expression of GLUT-1 in placenta basal membranes from GDM women in comparison with normal controls (23,24).…”
Section: Introductionmentioning
confidence: 99%